Design optimization of a snowboard performing an ollie - Huber, X.; Zwölfer, A.; Caillaud, B.; Rixen, D. J. (Sports Engineering, 2024)
The ollie, a fundamental manoeuver in snowboarding, serves as a basis for various tricks requiring high altitude and extended airtime. The maximum ollie height depends on the snowboard`s geometry and structural characteristics. In this study, the influence of these properties is investigated with a flexible multibody dynamics simulation, where the snowboard is modeled by geometrically non-linear finite elements, snow contact is considered by a penetration depth and velocity proportional normal force and ollie motion is achieved by imposing measured loads to the bindings. To maximize the height, a genetic optimization procedure is presented, which yields substantial improvements. Optimizing the camber line and the bending stiffness distribution yields enhanced performance. Less damping as well as lighter boards lead to higher jumps, no noteworthy correlation between axial stiffness and damping distribution and jump height was found, and the strain energy stored in the board during takeoff is a useful indicator for estimating ollie heights. Nevertheless, further investigations should take a more advanced and realistic rider interaction into account.